Green Transitions: Rethinking Political Economy in the Context of Climate Change - Basak Kus; Gregory Jackson (Regulation & Governance, 2025)
Although political economy (PE) has long engaged with environmental issues, climate change has remained at the margins of the field until very recently. This article argues that fully addressing the transformative challenges brought up by climate change requires a fundamental rethinking of core PE concepts related to the state, distributional struggles, economic growth, varieties of capitalism, and markets. Rather than treating the state as a neutral regulator or market facilitator, we conceptualize the green state as actively structuring transitions through mitigation policies, adaptation strategies, and the governance of just transition conflicts. Green transitions generate new distributional conflicts—within and across countries, between incumbent and emerging industries, and among social groups with unequal exposure to climate risks and transition costs. Climate policy also challenges growth-centered economic models, raising questions about the viability of green growth versus degrowth strategies. Different varieties of capitalism are evolving in response, with distinct institutional pathways shaping the speed and character of transition efforts. Finally, we critique market-based approaches that assume price mechanisms alone can drive decarbonization, highlighting the role of non-economic values, institutional constraints, and distributional struggles in shaping green markets. By linking climate change to core debates in comparative and international political economy, we identify new research agendas for understanding the uneven and contested pathways of green transitions across economic systems. This article, along with the others in this special issue on Greening the Economy: Toward a New Political Economy , aims to bridge some of these critical gaps.
Keywords: 330